The Surveillance After Extremity Tumor Surgery (SAFETY) trial: protocol for a pilot study to determine the feasibility of a multi-centre randomised controlled trial - David Wilson; Lehana Thabane; Gordon Guyatt; Mohit Bhandari; Michelle Ghert; P.D.Sander Dijkstra; Anthony Griffin; Robert Grimer; Arlene Manherz; Karim Masrouha; James Hayden; Paula McKay; et al. (BMJ Open)
Introduction Following the treatment of patients with soft tissue sarcomas (STS) that are not metastatic at presentation, the high risk for local and systemic disease recurrence necessitates post-treatment surveillance. Systemic recurrence is most often detected in the lungs. The most appropriate surveillance frequency and modality remain unknown and, as such, clinical practice is highly varied. We plan to assess the feasibility of conducting a multi-centre randomised controlled trial (RCT) that will evaluate the effect on overall 5-year survival of two different surveillance frequencies and imaging modalities in patients with STS who undergo surgical excision with curative intent.Methods and analysis The Surveillance After Extremity Tumor Surgery trial will be a multi-centre 2×2 factorial RCT. Patients with non-metastatic primary Grade II or III STS treated with excision will be allocated to one of four treatment arms1: chest radiograph (CXR) every 3 months for 2 years2; CXR every 6 months for 2 years3; chest CT every 3 months for 2 years or4 chest CT every 6 months for 2 years. The primary outcome of the pilot study is the feasibility of a definitive RCT based on a combination of feasibility endpoints. Secondary outcomes for the pilot study include the primary outcome of the definitive trial (overall survival), patient-reported outcomes on anxiety, satisfaction and quality of life, local recurrence-free survival, metastasis-free survival, treatment-related complications and net healthcare costs related to surveillance.Ethics and dissemination This trial received provisional ethics approval from the McMaster/Hamilton Health Sciences Research Ethics Board on 7 August 2019 (Project number 7562). Final ethics approval will be obtained prior to commencing patient recruitment. Once feasibility has been established and the definitive protocol is finalised, the study will transition to the definitive study.Trial registration NCT03944798; Pre-results.